Diversitas Pendidikan Multidimensional dalam Pertunjukan Kentongan Bambu Laras Banyumas Jawa Tengah - Rifky Fandanu; Wahyu Lestari; Suharto Suharto (Universitas Negeri Surabaya, 2021)
This study aims to identify the Kentongan Bambu Laras show and explore the contextualization of educational diversity in the Kentongan Bambu Laras performance. This study uses a qualitative method to recontextualize educational diversity in Kentongan Bambu Laras, Patikraja Village, Patikraja District, Banyumas Regency, Central Java. Data collection techniques include observation, interviews, documentation, and literature study. The data obtained were analyzed with a musicological approach used to analyze the form of Kentongan Bambu Laras performance from how to play and form music (form) and organology (instrumentation). The results showed that the value of honesty, discipline value, hard work value, and creative value were found in the Kentongan Bambu Laras performance. Furthermore, the recontextualization of multidimensional education lies in the instrumentation and complexity of the performances to develop physical or motor skills, perceptual, intellectual, emotional, social, creativity.